The relationship and different C4 Kranz anatomy of Bassia eriantha and Bassia eriophora, two often confused Irano-Turanian and Saharo-Sindian species - Akhani, Hossein; Khoshravesh, Roxana (Phytotaxa, 2013)
The circumscription and generic status of Bassia eriantha (≡ Londesia eriantha) and B. eriophora have often been confused in the literature. The reason is their extreme superficial similarity and phenology. In a multidisciplinary approach, we investigated both in the field, by cultivation in the laboratory, and performed anatomical, ultra-structural and molecular studies to clarify their taxonomy and relationships. Both species are not only geographically and morphologically distinct by reliable and constant characters, but surprisingly also have different anatomical C4 Kranz types and occur in different clades using ITS nrDNA sequence analysis. Using the recent broad circumscription of the genus Bassia they belong to Bassia but in different clades. In spite of their rather well distinct geography, the two species are sympatric in the south-eastern Iran and south Afghanistan. Bassia eriantha as an Irano-Turanian species occurs disjunctly as Irano-Turanian enclave in south Sinai, Jordan and W Saudi Arabia as a second sympatric range co-occurring with B. eriophora.